Effect of respiratory muscle strengthening on rowing performance - Priyashanthi Perera, Angage Dilani; Ariyasinghe, Anoja; Kariyawasam, Anula (Asian Journal of Medical Sciences, 2020)
Background: Respiratory muscle training (RMT) has been proposed as a beneficial means of improving respiratory muscle strength (RMS) and respiratory muscle fatigue (RMF) in athletes. Aims and Objective: The aim of this study was to determine the effects of a 12-week specific RMT program on the RMS, RMF and rowing ergometer performance in highly- trained rowers. Materials and Methods: Twenty professional rowers aged 20-35 years were recruited for the study during the competitive period and randomly grouped into an experimental (n=11) or control (n=9) group. Baseline measurements of maximal inspiratory and expiratory mouth pressures were obtained with a portable handheld mouth pressure meter while performance was assessed by 2000m and 5000m rowing ergometer machine. Subsequently rowers in the experimental group were prescribed a novel RMT program comprising of specific breathing and abdominal muscle exercises while the control group was prescribed a “general exercise program” for non- respiratory muscles for a 12-week period. RMF was assessed by calculating the difference between the pre-exercise and post-exercise mouth pressures. Results: Respiratory muscle strength improved overtime in the experimental and the control group following the respective training programs (p<0.05) with the experimental group showing higher RMS and lower RMF. However, there were no statistically significant differences in RMS and RMF between the two groups (P>0.05). More importantly, rowing ergometer performance improved significantly in the experimental group compared to the control (p<0.01). Conclusion: The results suggest that the novel RMT program had a significant effect in improving rowing performance, although the effect on RMS and RMF was not significant.